When Anger Motivates: Approach States Selectively Influence Running Performance - Giles, Grace E.; Horner, Carlene A.; Anderson, Eric; Elliott, Grace M.; Brunyé, Tad T. (Frontiers in Psychology, 2020)
Emotional states are thought to influence athletic performance. Emotions characterized by high arousal enhance exercise performance. Extant research has focused on the valence and arousal dimensions of emotions, but not whether the motivational dimension (the extent to which the emotion engenders approach or avoidance behaviors) influences exercise performance. Two studies aimed to determine whether films and music chosen to induce approach- (i.e. anger), avoidance- (i.e. fear), and neutral-oriented emotions would successfully induce their intended emotional states (Study 1) and whether anger and fear emotion inductions would influence two-mile time trial performance (Study 2). In Study 1, the films and music successfully induced their intended emotions. In Study 2, run time and perceived level of exertion did not differ between emotions across all participants or among faster-running participants per a median split. However, among slower-running participants, the anger induction increased two-mile running speed relative to the neutral induction. These findings suggest that emotions eliciting approach-related motivational states may improve exercise performance, particularly in slower runners.